Supervisi Akademik Meningkatkan Kompetensi Pedagogik Guru - Mujiono, Heri (Universitas Negeri Surabaya, 2020)
The condition of the teacher at SDN Kepanjen 2 shows far from ideal conditions. The results of preliminary surveys conducted by researchers in the execution of teachers ' duties, seven aspects of pedagogic competence teachers have not seen showing the skills of teachers in carrying out learning. Academic supervision is a selected action researcher to help teachers develop pedagogic skills of the teacher. This research is done cycle by cycle according to the concept of research action, planned there are 2 cycles with each cycle implemented measures planning, implementation, observation, reflection. Data collection techniques used in research using observations, interviews and documentation studies. The results of data analysis obtained exposure that proves that of the seven competencies that are targeted to research obtained an average value increase of 86%. So it can be concluded that the application of academic supervision can improve the pedagogic competence of teachers.